Using Padlet to Improve Students' Personal Letter-Writing Skills - Ferawati, Nur; Baa, Sultan; Asma, Nurul (ETDC: Indonesian Journal of Research and Educational Review, 2022)
At the SMK level, mastery of English content involves four language skills: listening, speaking, reading, and writing. Students frequently struggle with the four language skills mentioned above when learning English. Up to 75% of students at SMK Maarif NU Doro Vocational School continue to perform below KKM. The author decided to explain the subject of the analysis of the student's abilities to produce personal letter texts since it really caught his or her attention. The goal to be achieved in this research is to improve students' ability to compose a personal letter text. The technique used in this research is to make observations and test student performance in the form of an online written test. The student scores from the evaluation of the written test in the first cycle were 15 students (62.5%) who had reached the KKM. In the assessment of product results in the form of writing a personal letter and then sending it via a Padlet, 23 students (95.8%) met the KKM. At the end of the cycle, on the summative test, as many as 20 (80.2%) students passed the summative test without doing any remedial. As suggested, the implementation of online learning activities using the Padlet link to improve students' ability to write texts in the form of personal letters.